(untitled) (Journal of Green Business School, 2025)
Tourism today has a clear negative impact on the environment. Along with other stakeholders, visitors are increasingly concerned about environmental deterioration, and as awareness of this issue grows, green practices in tourism emerge. The main goal of this study is to investigate how various aspects of green practices in restaurant operations relate to one another. Personal interviews and a random sampling technique were used to gather data. Thirty-one cases were selected for data collection, and an analytical model was applied to analyze the collected data. Correlation analysis is used to determine the nature of the relationships between the variables, while factor analysis helps identify the principal variables. The top three factors identified in the study are "green steps," "recycling initiatives," and "green awareness." The study finds that while few restaurants can accurately define green practices, most engage in them, whether consciously or unconsciously, even though these practices are not fully developed. Significant relationships are found between green practices and the offered menu. A strong relationship is also uncovered between green practices and energy-saving programs. Among the green practices variables, several are strongly related to each other. Restaurants can focus on the variables that lead to the most effective green practices. J. of Green Business. Sch. Vol 6(1), Jan-Dec, 2023; pp 1- 18